Thermal Induced Structural Conductivity in LPCVD Polysilicon Film on Silicon Nitride/SiO2 Capped (100) Silicon - Lamichhane, Shobha Kanta; Akhtar, Jamil (Nepal Journal of Science and Technology, 2010)
Polysilicon (PS) grains are clustered in an order in the presence of thermal doping of boron in low pressure chemical vapour deposition (LPCVD). PS layer is lying on silicon nitride/silicon dioxide bed over (100) silicon substrate. The doped PS at different temperatures has been analyzed for the grain size and the shape of the clusters, employing non-contact mode atomic force microscopy (AFM). The grain size of the PS remains intact without a significant change with increasing doping temperature. A substantial increase in the cluster size and its density of the grains has been observed. The cluster formation mechanism induced by thermal variation is discussed in the context of recorded AFM images. The clusters lead to PS rings comprising of grains of the size of 100 nm. Keywords: Doping; Polisilico; Nanophysics; Grainsize; AFM; MEMS; LPCVD; SOI; Contactmode DOI: 10.3126/njst.v10i0.2901 Nepal Journal of Science and Technology Volume 10, 2009 December Page: 115-119